2020
DOI: 10.1371/journal.pcbi.1007409
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic transitions between higher order motifs underlie sustained asynchronous spiking in sparse recurrent networks

Abstract: A basic-yet nontrivial-function which neocortical circuitry must satisfy is the ability to maintain stable spiking activity over time. Stable neocortical activity is asynchronous, critical, and low rate, and these features of spiking dynamics contribute to efficient computation and optimal information propagation. However, it remains unclear how neocortex maintains this asynchronous spiking regime. Here we algorithmically construct spiking neural network models, each composed of 5000 neurons. Network construct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…SNNs were composed of both excitatory and inhibitory adapting exponential leaky integrate-and-fire neurons (AdEx) [27] connected with conductance-based synapses (Fig 1A; see methods). In previous work, we have shown that conductance-based synapses are crucial to accurately simulate neuronal integration of synaptic inputs—a critical consideration when evaluating structure-function hypotheses [8,28]. We conducted a grid search over a range of synaptic connectivity parameters defined by both excitatory and inhibitory connectivity and then quantified the outcome in SNN model behavior as connectivity parameter values changed (Fig 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SNNs were composed of both excitatory and inhibitory adapting exponential leaky integrate-and-fire neurons (AdEx) [27] connected with conductance-based synapses (Fig 1A; see methods). In previous work, we have shown that conductance-based synapses are crucial to accurately simulate neuronal integration of synaptic inputs—a critical consideration when evaluating structure-function hypotheses [8,28]. We conducted a grid search over a range of synaptic connectivity parameters defined by both excitatory and inhibitory connectivity and then quantified the outcome in SNN model behavior as connectivity parameter values changed (Fig 1B).…”
Section: Resultsmentioning
confidence: 99%
“…2A; see methods). In previous work, we have shown that conductance based synapses are crucial to accurately simulate neuronal integration of synaptic inputs-a critical consideration when evaluating structure-function hypotheses (Chambers and MacLean, 2016;Bojanek et al, 2020).…”
Section: Grid Search For Synaptic Architectures Producing Naturalistic Spikingmentioning
confidence: 99%
“…While some directly utilize structural data to derive pairwise connections, others infer functional networks from spiking activity across channels using pairwise relations such as cross-correlation or Granger causality (e.g. Bojanek et al, 2020;Dechery & Maclean, 2018;Schneidman et al, 2006;Jiang et al, 2017). In contrast, our motifclasses are determined from the triple correlation of the spike raster itself using combinations of temporal and spatial lags (Equation ( 1)).…”
Section: Discussionmentioning
confidence: 99%
“…Dickinson (1998); Kusters et al (2007); Hashemi et al (2012) to the network level (e.g. Kriener et al (2014); Tomov et al (2016); Bojanek et al (2020); Borges et al (2020); B. Santos et al (2021)).…”
Section: Introductionmentioning
confidence: 99%